2016
DOI: 10.1007/s12603-016-0723-0
|View full text |Cite
|
Sign up to set email alerts
|

A study on neuroprotective effects of curcumin on the diabetic rat brain

Abstract: The present study was aimed to study the neuroprotective therapeutic effect of curcumin on the male albino rat brain. Subarachnoid hemorrhage leads to severe mortality rate and morbidity, and oxidative stress is a crucial factor in subarachnoid hemorrhage. Therefore, we investigated the effect of curcumin on oxidative stress and glutamate and glutamate transporter-1 on a subarachnoid hemorrhage-induced male albino rats. The curcumin commonly used for the treatment and saline used for the control. Curcumin (10 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 26 publications
5
9
0
Order By: Relevance
“…Evidence indicates that curcumin can ameliorate pathologies associated to amyloid-β and recover p-Tau-related pathologies in animal models [32,33]. Also, curcumin has been shown to reduce the gene expression of insulin receptor and insulin receptor substrate-1 in the hippocampus [34][35][36]. Consistently, our results indicate that the combination of exercise and curcumin synergistically improves cognitive function in OLETF rats or inflammation response in OLETF intestines.…”
Section: Discussionsupporting
confidence: 83%
“…Evidence indicates that curcumin can ameliorate pathologies associated to amyloid-β and recover p-Tau-related pathologies in animal models [32,33]. Also, curcumin has been shown to reduce the gene expression of insulin receptor and insulin receptor substrate-1 in the hippocampus [34][35][36]. Consistently, our results indicate that the combination of exercise and curcumin synergistically improves cognitive function in OLETF rats or inflammation response in OLETF intestines.…”
Section: Discussionsupporting
confidence: 83%
“…The observed increase in GR activity in response to post-treatment with CUR after a QUIN lesion may confer to the cell the ability to regenerate the appropriate amount of GSH once it has been oxidized. Similar results were reported in the hippocampus of rats subjected to subarachnoid hemorrhage, in which an increase in GR activity was found in response to treatment with CUR (100 mg/kg) for one week [50]. The reduction of GSSG, catalyzed by GR, consumes NADPH, so it is necessary to maintain optimal levels of this cofactor during the oxidizing event.…”
Section: Discussionsupporting
confidence: 80%
“…Meanwhile, reactive oxygen species (ROS) can effectively activate the NF-κB p65 pathway, suggesting that excessive oxidative stress plays a catalytic role in inflammatory response [33]. In the brain, SOD and MDA were indicated that they could regulate the glutamate tansporters-1 which injures the neuronal [34]. It has been confirmed in large number of literatures that the activity of SOD was decreased and the expression of MDA was increased in the cerebral cortex in diabetic condition.…”
Section: Discussionmentioning
confidence: 97%